The reasons for atheism, its effects, and its refutation in the Quranic and intellectual perspective - Muhammad Amdad Ullah; Dr Farhadullah; Dr. Zia Ur Rehman (Journal of Religion and Society, 2025)
The paper examines the concept of atheism (al-Ilḥād) in terms of its linguistic origin, history, and recent practices with a focus on its influence on Muslim communities. Atheism, which initially meant deviation or rejection of the straight way has developed into a controlled rejection of God, revelation and the afterlife. The studies trace their origins to the work of philosophers of the West, materialism, humanism and popularization of Darwinism theory of evolution, which provided atheism with a system of ideas. The article has pointed out the role of the digital age especially the emergence of the internet and social media which has increased the speed of atheistic thought dissemination throughout the world. The act of decontextualizing the Quranic verses and falsifying the religious ideas and posing science as an alternative to Gods revelation has made inroads into the lives of young people, particularly those who are not well grounded in religion. The paper divides atheism into intellectual atheism, which is based on the abuse of reason and science; and psychological atheism, which is based on irrational desires and denial of moral prohibitions. Other differences like absolute atheism, naturalistic atheism, and practical atheism are also addressed. The most significant reasons are considered to be the misinterpretation of scientific advancement, the impact of the Western philosophy, the moral and practical contradictions within the religious representatives, the absence of religious education, and the negligence of parents in the upbringing process. Also, materialism, invasion of western culture and the insufficiency of the Islamic institutes in answering the questions of the modern times have all helped in this increasing trend. The study points out that to legitimize against atheism; rational arguments are not enough, but spiritual healing and moral reforms are also needed. The Quran and Sunnah give thorough answers to all objections and it has been established that science applied properly does not contradict but completes the revelation of God. Furthermore, the development of children based on a sound religious and intellectual base, the formation of a moral character and the use of modern media as the means to develop the authentic Islamic discourse are the necessary solutions. Finally, the paper comes to the conclusion that atheism is not the rejection of God but a more spiritual and intellectual perversion. The real remedy is the rediscovery of Quranic knowledge, the quality of synthesizing religion and knowledge and the actual practicing of what Islam teaches on individual and communal life. Without such actions, societies can only protect themselves against the devastating tides of atheism and be spiritually withstanding. Keywords: Atheism, Qur’an, Modernity, Materialism, Philosophy, Education, Faith Crisis